The Impact of Modic Changes on Preoperative Symptoms and Clinical Outcomes in Anterior Cervical Discectomy and Fusion Patients - James D. Baker; Garrett K. Harada; Youping Tao; Philip K. Louie; Bryce A. Basques; Fabio Galbusera; Frank Niemeyer; Hans-Joachim Wilke; Howard S. An; Dino Samartzis (Neurospine, 2020)
Objective To assess the impact of Modic changes (MC) on preoperative symptoms, and postoperative outcomes in anterior cervical discectomy and fusion (ACDF) patients. Methods We performed a retrospective study of prospectively collected data of ACDF patients at a single institution. Preoperative magnetic resonance imagings were used to assess the presence of MC. MC were stratified by type and location, and compared to patients without MC. Associations with symptoms, patient-reported measures, and surgical outcomes were assessed. Results A total of 861 patients were included, with 356 patients with MC (41.3%). MC more frequently occurred at C5–6 (15.1%), and type II was the most common type (61.2%). MC were associated with advanced age (p < 0.001), more levels fused (p < 0.001), a longer duration of symptoms, but not with specific symptoms. MC at C7–T1 resulted in higher postoperative disability (p < 0.001), but did not increase risk of adjacent segment degeneration or reoperation. Conclusion This study is the first to systematically examine the impact of cervical MC, stratified by type and location, on outcomes in ACDF patients. Patients with MC were generally older, required larger fusions, and had longer duration of preoperative symptoms. While MC may not affect specific outcomes following ACDF, they may indicate a more debilitating preoperative state for patients.